The case of professors in 1821 at St. Petersburg University: New interpretations - T.N. Zhukovskaya (Ученые записки Казанского университета: Серия Гуманитарные науки)
The academic conflict of 1821 at St. Petersburg University became a manifestation of the crisis of the liberal university model borrowed in 1802–1804 from Germany and was reflected in the first university statutes. This model failed to provide the independence of thinking and conduct in the small academic society or the status of the Russian university in the system of state institutions, which remained uncertain. In 1821, an attempt was made to replace the secular university with the clerical one, fully controlled from the outside, by the police department. This university in its pure form did not exist anywhere in Europe, but by 1821 it developed as an image in the program texts of M.L. Magnitsky and D.P. Runich, the ideologists of the counter reforms. The case of professors denounced the crisis of the former model of university management through its trustees, who in the previous two decades ensured the development of university centers by their authority and relations with Europe. This type of trustees was embodied by A. Chartoryisky in Vilna, S. Pototsky in Kharkiv, N.N. Novosiltsov and S.S. Uvarov. They were replaced by trustees-auditors, the accusers of the discovered administrative problems in the structure of universities, abuses of their predecessors, and also the spirit of “free-thinking and godlessness” found by them in teaching, which allegedly threatened the strength of the state. Audit as a special style of administration, approved in the field of education at the turn of the 1820s, corresponded to the methods of direct control in the new governorships created in the last years of the reign of Alexander I. This testifies to the regularity of the phenomenon of D.P. Runich and M.L. Magnitsky, but still does not explain the collapse of the career of the auditors and the demoralizing effect of the case of professors on the university society.